New families of solitary pattern solutions of the nonlinear dispersive K(n, m, k) equations - İnç, Mustafa (Verlag Z Naturforsch, 2004)
In this paper we shall derive new solitary pattern solutions of the nonlinear dispersive KdV equation (shortly called K(n,m,k)) by use of simple methods. The properties of these K(n,m,k) equations are shown in figures.
Keywords: solitary pattern; solitary wave solution; nonlinear dispersion